PERAN HUMAS DALAM PENGEMBANGAN PENDIDIKAN TINGGI - Musyarrofah, Mifrohatul (Idaarah: Jurnal Manajemen Pendidikan, 2018)
Currently the growth of the Internet indirectly also requires PR practitioners to develop their communication media. Education is a very is important aspect of the implementation of human rights, the implementation of the right is done every country in order to achieve the national goals and goals of the country concerned. According to Onong, Public Relations or Public Relations is a two-way communication between the organization with its public or its audience, both internal and external public, in order to support the organization's management functions and objectives, by enhancing co-operation and the fulfillment of common interests, Education is a very important a aspect of the implementation of human rights, the implementation of the right is carried out by each country in order to achieve the national goals and objectives of the country concerned. Indonesia is one of the countries that recognize and protect human rights in education. While universities in Indonesia during the reform era still continue to experience a very complicated issue, with the problems raised a variety.